Analysis of Learning Obstacles of Junior High School Students on The Topic of Circle - Ulfa, Nadia; Jupri, Al; Darhim; Kartika (Proceeding International Conference on Science and Engineering, 2020)
Geometry is one of the subjects in mathematics school that is important to learn, because through geometry, almost every daily problem can be solved. However, the achievements of Indonesian students in the field of geometry are still relatively low. This study aims to identify the possibility of students’ learning obstacles in one area of geometry, which is circle subject. The method used in this study was qualitative research method with survey-based research design, involved 30 eight-grade students from a junior high school in Bandung. The data were collected by triangulation method using an instrument test consisting of tests of students mathematical comprehension ability that is related to circle subject, and the non-test instruments used consist of collection of observations, guidelines for student interviews, and study documents. Results showed that there were identified any types of learning obstacle caused by epistemological obstacle among others (1) learning obstacle related to the concept of sector caused by an error in the perspective of students, (2) learning obstacle related to the form of geometrical representation from the central angle of the circle caused by the student’s limited knowledge of the central angle and chord of the circle. In addition, also found types of learning obstacle caused by didactical obstacle, among others (1) learning obstacle related to communication skills in presenting the definition of sector concept caused by not creating discussion and presentation activities when learning takes place, and (2) learning obstacle related the concept of the relationship between the diameter with chord of the circle caused by the presentation of material that is less detailed either provided by the teacher or presented in the source book used.